Granulocyte dynamics: a key player in the immune priming effects of crickets - Cho, Youngwoo; Cho, Saeyoull (Frontiers in Immunology, 2024)
This study investigates immune priming effects associated with granulocytes in crickets through a comprehensive analysis. Kaplan-Meier survival analysis reveals a significant contrast in survival rates, with the heat-killed Bacillus thuringiensis (Bt)-primed group exhibiting an impressive ~80% survival rate compared to the PBS buffer-primed group with only ~10% survival 60 hours post live Bt infection. Hemocyte analysis underscores elevated hemocyte counts, particularly in granulocytes of the killed Bt-primed group, suggesting a correlation between the heat-killed Bt priming and heightened immune activation. Microscopy techniques further explore granulocyte morphology, unveiling distinctive immune responses in the killed Bt-primed group characterized by prolonged immune activation, heightened granulocyte activity, phagocytosis, and extracellular trap formation, contributing to enhanced survival rates. In particular, after 24 hours of injecting live Bt, most granulocytes in the PBS buffer-primed group exhibited extracellular DNA trap cell death (ETosis), while in the killed Bt-primed group, the majority of granulocytes were observed to maintain highly activated extracellular traps, sustaining the immune response. Gene expression analysis supports these findings, revealing differential regulation of immune-related genes such as antibacterial humoral response, detection of bacterial lipopeptides, and cellular response to bacteria lipopeptides. Additionally, the heat-killed Bt-primed group, the heat-killed E. coli-primed group, and the PBS-primed group were re-injected with live Bt 2 and 9 days post priming. Two days later, only the PBS-primed group displayed low survival rates. After injecting live Bt 9 days later, the heat-killed E. coli-primed group surprisingly showed a similarly low survival rate, while the heat-killed Bt-primed group exhibited a high survival rate of ~60% after 60 hours, with actively moving and healthy crickets. In conclusion, this research provides valuable insights into both short-term and long-term immune priming effects in crickets, contributing to our understanding of invertebrate immunity with potential applications in public health.